2022
DOI: 10.2478/ata-2022-0029
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Prediction of Excavating Force and Power of Chain Type Trenching Machine

Abstract: A mathematical analysis was done to find out the factors that affect the excavating force and power of a chain type trenching machine. The mathematical analysis showed that the excavating force and power of the chain type trenching machine are affected by tool cutting speed, tool-cutting angle, angle between cutting movement and vertical direction, trench depth and width, coefficient of friction between soil and metal, soil cohesion resistance, and soil specific weight. The results of field experiments showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Some mathematical models were used to describe the performance of the trenching machines. Ghonimy et al (2022) concluded that the theoretical excavation force calculated by the mathematical model was lower than the actual excavating force by 4.0 kN and 3.5 kN for the 1.2 m and 1.5 m trench depths, respectively, for chain-type trenching equipment. And at trench depths of 1.2 m and 1.5 m, respectively, the theoretical excavation power was lower than the actual excavating power by 3.8% and 2.8%.…”
Section: Introductionmentioning
confidence: 90%
“…Some mathematical models were used to describe the performance of the trenching machines. Ghonimy et al (2022) concluded that the theoretical excavation force calculated by the mathematical model was lower than the actual excavating force by 4.0 kN and 3.5 kN for the 1.2 m and 1.5 m trench depths, respectively, for chain-type trenching equipment. And at trench depths of 1.2 m and 1.5 m, respectively, the theoretical excavation power was lower than the actual excavating power by 3.8% and 2.8%.…”
Section: Introductionmentioning
confidence: 90%